EPIPHYTE RESPONSE TO WOODLAND HABITAT CONDITION ASSESSED USING COMMUNITY INDICATORS: A SIMPLIFIED METHOD FOR SCOTLAND'S TEMPERATE RAIN FOREST. (9th November 2020) - Brosnan, V.; Ellis, C. J.
Abstract : National vegetation classification (NVC) has been widely applied as a framework for mapping and conserving plant species and community types. However, a limited availability of expertise has prevented NVCs from being developed and used in cryptogam-dominated systems, such as for temperate and boreal epiphyte communities. This study simplified a recent systematically sampled NVC, trialled for epiphyte communities in Scotland, by reducing the original list of 82 community indicators to 34 easily recognisable species (lichens, mosses and liverworts). These were subsequently sampled from woodland sites positioned in Scotland's temperate rain forest zone. Sites were positioned among localities in less intensively managed landscapes (northwest Scotland) through to peri-urban environments (southern Scotland), grouping sites for each locality based on a contrast in woodland temporal continuity (ancient or recent). The richness and diversity of epiphyte community indicators were compared with easily measured variables reflecting stand heterogeneity or ecological stability, and woodland temporal continuity, with air pollution as a covariable. Richness and diversity were significantly explained by the ecological stability of woodland stands, heterogeneity of the light environment, and nitrogen pollution. This demonstrates a tool that can be deployed by the non-specialist, with appropriate training, to quantify the condition of a woodland stand through consequences for its epiphytes in globally important temperate rain forest. The pattern of richness and diversity was consistent with the co-occurrence of particular indicator species, which represent the range of epiphyte community types supported by a woodland.